Pengaruh Kartu Prakerja dan Penetrasi Internet Terhadap Tingkat Penyerapan Tenaga Kerja Indonesia - Adryan Prasetyo; Lucky Rachmawati (Universitas Negeri Surabaya, 2022)
The purpose of the Pre-Employment Card program is to increase work competence and expected to make employment in Indonesia increase. However, the inequality of internet access can reduce the number of people who want to join this program. This study goals is to find out and explain the effect of the Pre-Employment Card program and internet penetration on the level of employment in Indonesia. The research method that used is explanatory quantitative method with the research population are all data for each province in Indonesia from each variable in the 2020 period and members of the population are all of the research sample. The data in this study are secondary data obtained from BPS Indonesia, APJII, and the Coordinating Ministry for the Economy. This study discovered that the Pre-Employment Card negatively affects the rate of employment and internet penetration does not affect the rate of employment. However, the Pre-Employment Card and internet penetration together affect the level of employment in Indonesia in 2020. Keywords: Pre-Employment Card, Internet Penetration, Employment